THE EFFECT OF JOB STRESS AND WORK-LIFE BALANCE ON EMPLOYEE WELL-BEING WITH EMPLOYEE ENGAGEMENT AS A MEDIATION VARIABLE ON GENERATION Z EMPLOYEES WORKING IN THE SPECIAL REGION OF YOGYAKARTA - Oktabrina Candy Artika; Nur Wening (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of job stress and work-life balance on employee well-being, with employee engagement as a mediating variable among Generation Z employees working in the Special Region of Yogyakarta. This research employed a quantitative approach using a survey method involving 96 respondents selected through simple random sampling. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that job stress has a negative and significant effect on employee well-being, while work-life balance has a positive and significant effect. Furthermore, job stress negatively affects employee engagement, whereas work-life balance positively influences employee engagement. Employee engagement is proven to have a positive and significant effect on employee well-being. In addition, employee engagement mediates the relationship between job stress and employee well-being and partially mediates the relationship between work-life balance and employee well-being. These findings suggest that reducing job stress and improving work-life balance are essential strategies for enhancing employee well-being, particularly among Generation Z employees. Strengthening employee engagement also plays a crucial role in promoting psychological well-being and sustainable performance in the workplace.